2022
DOI: 10.1055/s-0042-1755365
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathy as an Adjuvant to Standard Care in Moderate and Severe Cases of COVID-19: A Single-Blind, Randomized, Placebo-Controlled Study

Abstract: Objectives This study aimed to evaluate whether individualized homeopathic medicines have a greater adjunctive effect than adjunctive placebos in the treatment of moderate and severe cases of coronavirus disease 2019 (COVID-19). Methods The study was a randomized, single-blind, prospective, placebo-controlled clinical trial set in the clinical context of standard care. Intervention Patients of either sex, admitted in a tertiary care hospital, suffering from moderate or severe COVID-19 and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…[18][19][20] In multi-morbid conditions, lifestyle diseases, and a few surgical conditions, an integrative approach using homeopathy with standard care has shown some positive results, evident from a number of previously published research studies. [21][22][23] However, substantive evidence is still lacking. In the present two evidence-based case reports of DFUs treated with an integrative treatment approach of standard care and homeopathy, the healing arrived early and safely.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] In multi-morbid conditions, lifestyle diseases, and a few surgical conditions, an integrative approach using homeopathy with standard care has shown some positive results, evident from a number of previously published research studies. [21][22][23] However, substantive evidence is still lacking. In the present two evidence-based case reports of DFUs treated with an integrative treatment approach of standard care and homeopathy, the healing arrived early and safely.…”
Section: Discussionmentioning
confidence: 99%
“…Several interpretations could be inferred: (1) Camphora 1M could be inappropriate as a genus epidemicus. Later RCT studies have shown positive results with individualized treatment, viral nosode 30cH, Bryonia 30cH, Arsenicum album 30cH and Natrum muriaticum 2LM only, [43][44][45][46] though observational studies have pointed to other findings. 47,48 (2) The use of homeopathic medicine in a single dose might not be the most appropriate posology.…”
Section: Discussionmentioning
confidence: 99%
“…54 For this reason, an individualized homeopathy approach a priori could be more appropriate than applying genus epidemicus. 44,46 In less urgent circumstances, conducting controlled clinical trials or long-term observational studies could provide more robust responses to determine clinical effectiveness or lack thereof. Clinical trials conducted later in India and Brazil showed the effectiveness of Bryonia 30cH, the isotherapeutic 30cH and Natrum muriaticum 2LM.…”
Section: Discussionmentioning
confidence: 99%
“…The role of homeopathic preparations in preventing SARS-Cov-2 infection was described by Dr Rajesh Shah (India) and Dr Debadatta Nayak (India). Treatment of acute COVID-19 symptoms using individualised homeopathy was described by Dr Raj Manchanda (India) 12 and Dr Harleen Kaur (India), 13 while Dr Elizabeth Rice and Dr Eleni Krommidas (USA) described the outcome of a pilot study exploring the impact of individualised homeopathic treatment on 'long-COVID'.…”
Section: Further Clinical Researchmentioning
confidence: 99%